Polyphenolic characterization and chromatographic methods for fast assessment of culinary Salvia species from South East Europe - Cvetkovikj, I; Stefkov, G; Acevska, J; Stanoeva, J Petreska; Karapandzova, M; Stefova, M; Dimitrovska, A; Kulevanova, S (Elsevier BV, 2013)
Although the knowledge and use of several Salvia species (Salvia officinalis, Salvia fruticosa, and Salvia pomifera) can be dated back to Greek Era and have a long history of culinary and effective medicinal use, still there is a remarkable interest concerning their chemistry and especially the polyphenolic composition. Despite the demand in the food and pharmaceutical industry for methods for fast quality assessment of the herbs and spices, even now there are no official requirements for the minimum content of polyphenols in sage covered by current regulations neither the European Pharmacopoeia monographs nor the ISO 11165 standard. In this work a rapid analytical method for extraction, characterization and quantification of the major polyphenolic constituents in Sage was developed. Various extractions (infusion - IE; ultrasound-assisted extraction - USE and microwave-assisted extraction - MWE) were performed and evaluated for their effectiveness. Along with the optimization of the mass-detector and chromatographic parameters, the applicability of three different reverse C18 stationary phases (extra-density bonded, core-shell technology and monolith column) for polyphenolics characterization was evaluated. A comprehensive overview of the very variable polyphenolic composition of 118 different plant samples of 68 populations of wild growing culinary Salvia species (S. officinalis: 101; S. fruticosa: 15; S. pomifera: 2) collected from South East Europe (SEE) was performed using HPLC-DAD-ESI-MS(n) and more than 50 different compounds were identified and quantified. With this work the knowledge about polyphenols of culinary Sage was expanded thus the possibility for gaining an insight into the chemodiversity of culinary Salvia species in South East Europe was unlocked.